Long-period astronomical forcing of westerlies' strength in Central Asia during Miocene climate cooling. - Frisch, Konstantin; Voigt, Silke; Verestek, Verena; Appel, Erwin; Albert, Richard; Gerdes, Axel; Arndt, Iris; Raddatz, Jacek; Voigt, Thomas; Weber, Yuki; Batenburg, Sietske J (PANGAEA, 2019)
The Aktau succession is located at 44.03°N and 79.30°E in the Ili Basin, south-east Kazakhstan. The dataset contains measurement results from the Middle to early Late Miocene part of the succession (total height: 372 m, lowermost sample: 0.29 m, uppermost sample: 370.94 m). Stable carbon and oxygen istopes and CaSO₄ content were derived from bulk rock measurements. The CaSO₄ content was determined by microwave digestions and ICP-OES analysis. The laser ablation U-Pb data was aquired from thin sections in order to obtain radiometric ages of carbonates along the Aktau succession.
Stable carbon and oxygen isotopes, calcium sulfate content, and laser ablation Uranium-Lead dating of the Miocene alluvial-lacustrine Aktau succession in south-east Kazakhstan
Keywords: Aktau succession; CaSO4 content; Ili Basin; Laser ablation U-Pb dating; stable carbon isotopes; stable oxygen isotopes